Organic food: a study on demographic characteristics and factors influencing purchase intentions among consumers in Klang Valley, Malaysia - Ahmad, Siti Nor Bayaah; Juhdi, Nurita (Canadian Center of Science and Education, 2010)
This study attempted to gain knowledge about consumers’ intention to purchase organic food products and their demographic characteristics. Data were collected in supermarkets within 3 different areas in Klang Valley, Malaysia using mall-intercept approach. A total of 177 respondents were generated. The data obtained from the survey were analyzed using chi-square test, ANOVA, correlation analysis and multiple linear regression tests. Result indicated that the intention to purchase organic products were heavily influenced by the perception on organic product worth of purchase and the belief on the safety and health aspect of the product. Respondents were divided into organic buyers and non-buyers categories. Among the organic buyers majority consumers believed organic food to be healthier, tastier and better for environment compared to conventional food.